Social Cohesion for Sustainable Urban Development: Evidence From Kediri City - Wicaksono , Adi; Darmawan , Salim (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
Social cohesion is becoming a key issue in efforts to achieve well-functioning societies at the local and national levels. Many academics and institutions consider social cohesion as a key driver to enable societies to achieve their well-being, reduced inequality and greater prosperity. Social cohesion is formed from harmony and tolerance. Kediri City's Religious Harmony Index (IKUB) increased consistently from 3.97 in 2021 to 4.47 (2022), then 4.55 (2023), and 4.56 in 2024, indicating a very high level of harmony. In addition, Kediri City has also managed to maintain its position as one of the top 10 most tolerant cities in Indonesia for several consecutive years. In terms of the economy, Kediri City's GRDP growth rate is 2.50% (2021), 3.96% (2022), 1.92% (2023), and rising again to 3.43% in 2024. Meanwhile, investment realization in Kediri City shows positive growth with a total of IDR 1.54 trillion in 2024-up from IDR 1.34 trillion in 2023-or exceeding the annual target by 15.36%. This study seeks to examine the extent to which social cohesion determines economic development in Kediri City. To that end, a structured literature review was conducted with reference to the five dimensions of social cohesion proposed by Jane Jenson (1998). The study found that there is a strong relationship between social cohesion and economic growth at the local level. It is important for municipalities to provide a conducive environment that allows them to optimally benefit from local business growth in various sectors, stable investment, as well as more tourism visits